Adequacy of Undergraduate Orthopedic Training at a Nepalese Medical Academy - Tamrakar, Rojan; Basnyat, Sagun; Gyawali, Bidur; Bhatta, Toya Raj; Shah, Gajendra Mani; Acharya, Balakrishnan; Shrestha, Suman Kumar; Pradhan, Nabees Man Singh (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: A basic familiarity with orthopaedic disorders is important for all medical school graduates. The purpose of this study is to assess the adequacy of undergraduate orthopaedic knowledge among the first batch interns of our academy. Methods: The validated basic cognitive examination designed by Freedman and Bernstein, consisting of 25 short answer questions was administered to the first batch interns. Overall scores and responses to the individual questions were analyzed. The recommended passing score of 73.1 per cent as suggested by Freedman and Bernstein was considered. The overall unweighted and weighted scores were calculated. The questions were also separated into anatomy, general orthopedics and trauma groups. The Microsoft Office Excel 2007 was used for the statistical analysis. Results: Forty eight interns appeared the examination with the mean scores obtained was 58.79 per cent. Forty five interns (94 per cent) failed to demonstrate basic competency on the examination. The overall weighted score for all interns was 61 per cent. Forty two (88 per cent) of the 48 interns failed the examination even when the questions were weighted. The average scores in the general orthopedics, trauma and anatomy groups were 49, 76 and 54.6 per cents respectively. Conclusion: Majority (94 percent) of the first batch interns failed the validated basic musculoskeletal examination. Curriculum and teaching methods is inadequate or inappropriate and should be re-evaluated to address this problem.